Prediction of combination therapy efficacy in patients with locally advanced squamous cell oropharyngeal carcinoma - I. A. Bakhronov; G. V. Kakurina; L. D. Zhuykova; I. V. Kondakova; E. L. Choynzonov (Сибирский онкологический журнал)
Background. Oropharyngeal squamous cell carcinoma (OPSCC) is characterized by late-stage diagnosis and high rate of mortality. Combined modality treatment including preoperative chemoradiotherapy (CRT) is the standard of care for OPSCC. The search for criteria for predicting the efficacy of preoperative chemoradiotherapy with a view to prescribe it to those patients for whom it is really indicated and will be effective remains challenging. The aim of the study was to identify serum actin-binding proteins that can predict preoperative therapy efficacy in patients with OPSCC. Material and methods. Blood serum from 45 patients with stage II–IV OPSCC was studied. all patients received preoperative chemotherapy with paclitaxel and carboplatin. Radiation therapy in a standard mode was given 2 weeks after chemothetapy. serum levels of actin-binding proteins (CAP1, fascin, ezrin, gelsolin, and profiling) were determined before treatment using ELISA. Results. complete or partial response to preoperative CRT was achieved in 27 patients. Disease progression or stabilization was observed in 18 patients. A comparison of the serum levels of actin-binding proteins before treatment with those obtained after preoperative CRT showed that the serum level of ezrin was lower in patients who did not respond to preoperative CRT than in patients with partial or complete response to therapy. ROC-analysis showed that the serum level of ezrin of less than 2.50 ng/ml can predict the tumor response to CRT as unfavorable (less than 75 % according to the RECIST scale). The sensitivity was 72 % and the specificity was 71 %. Conclusion. Determination of the serum level of ezrin in patients with OPSCC has a predictive value in relation to preoperative chemoradiotherapy.